Comparative genomics provides insights into the lifestyle and reveals functional heterogeneity of dark septate endophytic fungi - Dániel G. Knapp (Nature Portfolio, 2018)
Abstract Dark septate endophytes (DSE) are a form-group of root endophytic fungi with elusive functions. Here, the genomes of two common DSE of semiarid areas, Cadophora sp. and Periconia macrospinosa were sequenced and analyzed with another 32 ascomycetes of different lifestyles. Cadophora sp. (Helotiales) and P. macrospinosa (Pleosporales) have genomes of 70.46 Mb and 54.99 Mb with 22,766 and 18,750 gene models, respectively. The majority of DSE-specific protein clusters lack functional annotation with no similarity to characterized proteins, implying that they have evolved unique genetic innovations. Both DSE possess an expanded number of carbohydrate active enzymes (CAZymes), including plant cell wall degrading enzymes (PCWDEs). Those were similar in three other DSE, and contributed a signal for the separation of root endophytes in principal component analyses of CAZymes, indicating shared genomic traits of DSE fungi. Number of secreted proteases and lipases, aquaporins, and genes linked to melanin synthesis were also relatively high in our fungi. In spite of certain similarities between our two DSE, we observed low levels of convergence in their gene family evolution. This suggests that, despite originating from the same habitat, these two fungi evolved along different evolutionary trajectories and display considerable functional differences within the endophytic lifestyle.